Non-symmetric mechanophores prepared from radical-type symmetric mechanophores: bespoke mechanofunctional polymers. Issue 23 (22nd February 2021) - Yanada, Kosaku; Kato, Sota; Aoki, Daisuke; Mikami, Koichiro; Sugita, Hajime; Otsuka, Hideyuki
Abstract : Non-symmetric radical-type mechanophores were synthesized by molecular crossing between two radical-type mechanophores toward the design of bespoke mechanofunctional polymers. Abstract : A non-symmetric radical-type mechanophore (CF/ABF) was synthesized by molecular crossing between two radical-type mechanophores. The thermal stability and mechanoresponsiveness of CF/ABF were found to be tunable by altering the properties of the parent RMs. The CF/ABF-centred polymers showed mixed mechanochromism derived from the simultaneous generation of two radical species.